Extended resection of the trachea in a patient with cicatricial tracheal stenosis after tracheostomy complicated with esophageal-tracheal fistula and extensive defect of the frontal tracheal wall - Khudaybergenov, Shukhrat; Eshonkhodjaev, Otabek; Abdusalomov, Sodiqjon; Amanov, Bakhrom (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
We present a case of one-stage radical surgical treatment of a 24-year-old female patient with cicatricial granulating tracheal stenosis after tracheostomy complicated by esophageal-tracheal fistula and an extensive defect of the anterior wall of the trachea after numerous unsuccessful attempts to correct the narrowing of the trachea and eliminate the fistula by endoscopic and open surgical techniques. The patient underwent extended tracheal resection with end-to-end anastomosis with liquidation of the esophageal-tracheal fistula and elimination of the defect of the anterior wall of the trachea by cervical access.